Prevalence and factors associated with sexual dysfunction among middle-aged women in a multi-ethnic country: a cross sectional study in Malaysia - Tey, Yin Yee; Ching, Siew Mooi; Maharajan, Mari Kannan; Lee, Kai Wei; Chow, Zhen Yee; Chua, Pei Wen; Tan, Chin Xuan; Lim, Shi Nie; Tan, Chun Han; Thew, Hui Zhu; Ramachandran, Vasudevan; Hoo, Fan Kee (Academy of Family Physicians of Malaysia, 2022)
Introduction: This study aimed to determine the prevalence and factors associated with female sexual dysfunction in an outpatient clinic in Malaysia. Methods: The study was conducted among female patients aged 50 years and older who attended the outpatient clinic of a public hospital in Malaysia. A self-administered questionnaire was used that was based on the Malay version of the Female Sexual Function Index questionnaire. The predictors of female sexual dysfunction were identified using multivariate logistic regression analysis. Results: A total of 263 females were recruited in this study, with a mean age of 60.6 ± 6.7 years. The distribution of the respondents’ ethnicities was mostly Malay (42.2%), followed by Chinese (41.8%) and Indian (16.0%). The prevalence of female sexual dysfunction among participants was 68.8%. The prevalence of the subscales of female sexual dysfunction was as follows: desire (85.2%), satisfaction (74.9%), arousal (71.1%), lubrication (66.9%), pain (61.2%), and orgasm (60.8%). According to multivariate logistic regression, patients of Indian ethnicity had an increased risk of female sexual dysfunction (OR=16.60, 95% CI=2.54–108.63), and a higher frequency of sexual intercourse was correlated with a lower risk of female sexual dysfunction (OR=0.13, 95% CI=0.08–0.24). Conclusion: Seven-tenths of the middle-aged female patients attending the outpatient clinic suffered from female sexual dysfunction. Indian ethnicity and having a lower frequency of sexual intercourse were predictors of female sexual dysfunction. Future intervention studies are needed to address this problem.